Emergent God in Neutral Monism - Pereira, Alfredo [UNESP] (My University, 2024)
The aim of this paper is to dissociate Metaphysics and Theology. In Metaphysics, I propose a Neutral Monist foundation of the Being of Reality, which is, therefore, not material or ideal, but a cosmic field of possibilities that generates both domains. God is conceived as one possibility embedded in the Being of Reality that may or may not become actual, depending on conditions established by the evolution of the Cosmos. As far as we know, the conditions for the actualization of God are satisfied by human consciousness. The relation between the Being of Reality and its outcomes, as the realization of God in human society, is one of actualization of potentialities, as in Aristotelian philosophy. This approach leads to a Feuerbachian view of God as emergent in social conscious experience, achieving embodied expression in human social practices, from the legitimate symbolic message of prophets, in sacred texts, rituals, images, buildings, and social institutions implemented by religious organizations.
Keywords: Consciousness; Emergent; Energy; God; Neutral monism; Sentience